Depositional environment and organic matter enrichment mechanism of the lower cambrian shale in the southern Sichuan Basin - Lu, Bin; Hou, Du-jie; Zou, Cai-neng; Li, Xi-zhe; Gao, Ri-sheng; Wei, Heng-ye; Qiu, Zhen (Frontiers in Earth Science, 2025)
The Ediacaran-Cambrian transition was one of the most important periods in Earth’s history. Based on the analysis of lithofacies, mineral composition, total organic carbon major and trace elements, we have studied the depositional environment and organic matter enrichment mechanism of Qiongzhusi Formation shale in the southern Sichuan Basin. The results show that V/Cr, Ni/Co, U/Th, Mo-EF and U-EF values suggest stronger reducing conditions in black shale compared to grey shale, with anoxic conditions decreasing from the interior of the faulted-sag to its exterior. Mo-TOC crossplots and U-Mo covariation analyses indicate a moderately restricted environment during the deposition of the Qiongzhusi Formation. Ba/Al and biogenic barium (Baxs) suggest that the black shale had higher paleoproductivity than grey shale, and the faulted-sag interior higher paleoproductivity compared to that of the slope and outside faulted-sag. The Ti/Al ratio indicates a stable terrigenous input during deposition. The chemical index of alteration (CIA) values in the Qiongzhusi formation range mostly from 50 to 70, indicating low chemical weathering under a cold and arid climate. The Cd/Mo ratio and Co (μg/g) × Mn (%) plot indicate that upwelling had a minor influence in general. Overall, the organic matter enrichment in the Qiongzhusi Formation was primarily controlled by the redox conditions, which were influenced by the Mianyang-Changning faulted-sag. We proposed two depositional models for the Qiongzhusi Formation shale in the southern Sichuan Basin: (1) OM-enriched black shale, deposited under anoxic-suboxic conditions, experiencing low chemical weathering, cold and arid climate and high paleoproductivity; (2) OM-lean grey shale, deposited under suboxic-oxic conditions, with low chemical weathering, a cold and arid climate and low paleoproductivity.